Volcanic and environmental influences of Mt. Fuji on the δ13C of terrestrially-derived n-alkanoic acids in sediment from Lake Yamanaka, central Japan. (May 2018) - Yamamoto, Shinya; Uchiyama, Takashi; Miyairi, Yosuke; Yokoyama, Yusuke
Highlights: Molecular and stable carbon isotopic compositions of leaf wax n -alkanoic acids were examined in Lake Yamanaka sediment. The δ 13 C values of C30 acids reflect plant physiological responses to changes in water availability during the Holocene. The δ 13 C excursions of C24 –C28 acids at ca. 1750 and 1100 cal yr BP indicate a rise of C4 grass by the volcanic eruptions. Abstract: The recognition of vegetation changes induced by volcanic eruption is particularly important for paleoenvironmental studies in volcanic regions. In this study, we examined the molecular and stable carbon isotopic compositions (δ 13 C) of sedimentary leaf wax n -alkanoic acids from Lake Yamanaka at the northeastern foot of Mt. Fuji, central Japan, to distinguish volcanic effects on biomarker δ 13 C proxies from other environmental influences over the past 15, 000 years. The δ 13 C values of C30 acids showed a significant positive correlation with average chain length (ACL24–30 ), suggesting that δ 13 C reflects plant physiological responses to changes in water availability for C3 plants. The δ 13 C values of C30 acids showed patterns similar to those of Holocene stalagmite δ 18 O records in Chinese caves, indicating that variations in hydroclimate at the northeastern foot of Mt. Fuji are controlled by large-scale changes in Asian monsoon activity. In contrast, the δ 13 C values of C24 –C28 acids increased abruptly at ca. 1750 and 1100 cal yr BP, which coincide with eruptive events at the northeastern flank of Mt. Fuji. This suggests an increase in input from C4 plants, likely reflecting an increase in C4 Miscanthus grass, a pioneer species on volcanic deposits, following by the devastation of forest by the eruptions.